The Influence Of Golden Age Nutrition With Stunting Events In Toddlers In Panyabungan Village, Julu, Mandailing Regency Christmas 2022 - siti kholidah (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2022)
Stunting is a condition where children experience delays in growth caused by lack of nutritional intake for a long time. This study aims to determine the effect of nutrition during the golden age period with stunting in children under five in Panyabungan Julu Village, Mandailing Natal Regency in 2022. The type of this research was analytic observational with a cross sectional approach. The population is toddlers aged 2-5 years (25-59 months) as many as 36 toddlers. The sample in this study were 36 toddlers aged 2-5 years (25-59 months). Data analysis technique using chi square. The results obtained in this study were from 36 respondents, who received nutrition as many as 16 people (44.4%) with 3 people experiencing stunting (8.3%) and 13 people without stunting (36.1%). and who did not get as many as 20 people (55.6%) with 2 people experiencing stunting (5.6%) and 18 people not experiencing stunting (50%). Based on the statistical test with Chi-Square showed that the value of p = 0.045 < 0.05, that there was an effect of Golden Age Nutrition Giving with Stunting Incidence in Toddlers in Panyabungan Julu Village, Mandailing Natal District in 2022. It is recommended to the puskesmas to increase health promotion to improve health status.